Development of Character Education on Ibn Miskawaih's Thought - Darmawati Darmawati; Ambo Dalle; Fikri Haekal Amdar; Abdul Aziz Bin Mustamin (At-Ta'lim : Media Informasi Pendidikan Islam, 2020)
Abstract: Development of Character Education on Ibn Miskawaih's Thought.The focus of the problem in this study is how to develop character education in Ibn Miskawaih's view. This type of research is a library research method, in the form of character studies. The results found by the author were that Ibn Miskawaih himself acknowledged that the essence and function of education is to shape the human personality so that humans who have evil and praiseworthy characteristics are formed. According to Ibn Miskawaih, the nature and function of education is to shape the personality of the human being so that a person who has a commendable character is formed. Because basically human morals can be changed through education and the environment. Therefore, in its implementation character education can be designed by including character education values in the national education curriculum.